Investigation of motion tracker for IOT applications - Myat Hsu Zin (2016)
Human motion tracking technology is becoming popular for its functionality in many applications ranging from virtual reality to medicine. There are several approaches to motion tracker but inertial motion tracking which makes use of MEMS (microelectromechanical sensors) such as gyroscope, accelerometer and magnetometer. IMU (Inertial Motion Unit) is an electronic devices that measures the change in orientation, angular rate and the magnetic field surrounding the body. IMU used in this project contains all three sensors; gyroscope, accelerometer and magnetometer on board. In this project, author tested and experimented with different types of sensors to determine which would best suit the human motion tracking application and produce an accurate orientation angle. As gyroscope tends to drift, Kalman filter and complementary filter are implemented for data fusion of gyroscope and accelerometer and to provide a stable and accurate orientation angle. As magnetometer is easily affected by magnetic field around it, the readings from magnetometer are not accurate. Digital motion processor is explored to provide an accurate and stable orientation angle. As representing the angle in roll, pitch and yaw has gimbal lock problem, a quaternion representation approach is favourable